Grant Code Sanctions of Polri Members Who Have Disconnected The Court Binding Drug Abuse (Case Study Polres Cirebon) - Joseph Diko Reinol Panjaitan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This study aims to identify and understand the sanctions in the Code of Conduct Police officers and efforts to the implementation of sanctions against Alleged offenders alleged to have violated the code of Professional Ethics of Police, in the form of deeds has committed the crime of Abuse of Narcotics kind Sabu-shabu and cases criminal has received the Decision of the Court Of Sumber country, with an excerpt of Decision No. 394 / Pid.Sus / 2017 / PN.Sbr. October 19, 2017, which states the defendant initials S, proven legally and convincingly guilty of committing the crime of abuse of Narcotics Group I For Yourself and sentenced to imprisonment for six (6) months. This research was conducted in Cirebon. To the authors conducted a study with the title